Português Organic fertilizer application combined with seed inoculation using rhizobacteria on tomato yield and quality - Santos, Lívian Patrícia da Silva; Mota, Wagner Ferreira da; Pegoraro, Rodinei Facco; Polete Mizobutsi, Gisele; Nobre, Sérgio Avelino Mota; Soares, Marcela de Castro (Comunicata Scientiae, 2024)
Organic fertilizer application combined with seed inoculation using rhizobacteria enables increases in industrial tomato production. The objective of this work was to assess the synergistic effect of organic fertilizer application and seed inoculation with rhizobacteria on tomato yield and quality. A randomized complete block experimental design with four replication was used, in a 6×3 factorial arrangement consisted of six fertilizer sources (mineral fertilizer; cattle manure; and organic composts based on tomato, sugarcane bagasse, tomato + sugarcane; and tomato + sugarcane + banana stalk) and three different seed inoculation with rhizobacteria (a control, without inoculation; inoculation with RZB 18; and inoculation with LEMB 17). The evaluated fruit characteristics were: commercial and non-commercial yields; firmness; soluble solids content (SSC); industrial yield; titratable acidity (TA); SSC to TA ratio, and pH. The rhizobacteria significantly affected all evaluated characteristics. The highest mean industrial yields were obtained with the application of mineral fertilizer (7.59), tomato-based compost (7.99), and sugarcane bagasse-based compost (7.95 Mg ha-1). Although seed inoculation with rhizobacteria did not affect fruit yield and quality, organic composts based on tomato and sugarcane bagasse residues might be used as organic fertilizer for industrial tomato production.